Malnutrition and Frailty Are Critical Determinants of 6-Month Outcome in Hospitalized Elderly Patients With Heart Failure Harboring Surgically Untreated Functional Mitral Regurgitation - Miura, Masakazu; Okuda, Shinichi; Murata, Kazuhiro; Nagai, Hitoshi; Ueyama, Takeshi; Nakao, Fumiaki; Shimokawa, Mototsugu; Yamamoto, Takeshi; Ikeda, Yasuhiro (Frontiers in Cardiovascular Medicine, 2021)
Background: Hospitalized patients with acute decompensated heart failure (ADHF) frequently exhibit aggravating mitral regurgitation (MR). Those patients do not always undergo surgical mitral valve repair, but particularly in the elderly, they are often treated by conservative medical therapy. The present study was aimed to investigate factors affecting 6-month outcomes in hospitalized patients with HF harboring surgically untreated MR. Method: We screened the presence of MR in hospitalized HF patients between September 2017 and May 2020 in the Yamaguchi Prefectural Grand Medical (YPGM) center. At the time of discharge of these patients, individuals with surgically unoperated MR, including primary and secondary origin, were consequently recruited to this single-center prospective cohort study. The patients with severe MR who undergo surgical mitral valve treatment were not included in this study. The primary endpoint was all-cause readmission or all-cause death, and the secondary endpoint was HF-related endpoint at 6-month after discharge. Cox proportional hazard regression analyses were employed to assess the predictors for the composite endpoint. Result: Overall, 489 patients with ADHF were admitted to the YPGM Center. Of those, 146 patients (30% of total HF patients) (median age 83.5, 69 men) were identified as harboring grade Ⅱ MR or greater. Consequently, all recruited patients were diagnosed as functional MR. During a median follow-up of 186.0 days, fifty-five patients (38%) reached the primary or secondary endpoints (HF death and readmission in 31, other in 24). As a result of multivariate analysis, geriatric nutritional risk index (hazard ratio [HR] = 0.932; 95%confidence interval [CI] = 0.887-0.979, p = 0.005), age (HR = 1.058; 95%CI = 1.006-1.112, p = 0.027), and left ventricular ejection fraction (HR = 0.971; 95%CI = 0.945-0.997, p = 0.030) were independent predictors of all-cause death or all-cause admission. Body mass index (HR = 0.793; 95%CI = 0.614-0.890, p = 0.001) and ischemic heart disease etiology (HR = 2.732; 95%CI = 1.056-7.067, p = 0.038) were also independent predictors of the HF-related endpoints. Conclusion: Malnutrition and underweight were substantial predictors of adverse outcomes in elderly patients with HF harboring surgically untreated moderate to severe functional MR.